Familial four breakpoint complex chromosomal rearrangement as a cause of monosomy 9p22–>pter and trisomy 10p11.2–>pter and 11q21 analysed by dual and triple colour FISH. Issue 8 (August 1997) - Stankiewicz, P; Kostyk, E; Bocian, E; Stańczak, H; Parczewska, J; Piatkowska, E; Mazurczak, T; Pietrzyk, J J
Abstract : A familial four breakpoint complex chromosomal rearrangement involving chromosomes 9, 10, and 11 was ascertained through a child with dysmorphic features, hypertrophic cardiomyopathy, and hypotonia. A cryptic insertion, invisible in G banded chromosomes was identified by fluorescence in situ hybridisation (FISH) using chromosome specific libraries. Possible mechanisms of its formation as well as karyotype-phenotype correlation are discussed.